Agreeable trade with optimism and pessimism - Dominiak, Adam; Eichberger, Jürgen; Lefort, Jean-Philippe (Mathematical social sciences, 2012)
In this paper we extend the results on ex-ante agreeable trade of Kajii and Ui [Kajii, A., Ui, T., 2006. Agreeable bets with multiple priors. Journal of Economic Theory 128, 299-305] to the case of nonconvex Choquet preferences. We discuss the economic relevance of the main result for the existence of speculative trade under ambiguity. Following Haller [Haller, H., 1990. Non-market reopening, timeconsistent plans and the structure of intertemporal preferences. Economics Letters 32, 1-5] we also elaborate the relevance of updating preferences upon arrival of public information for the potential of re-contracting initial contingent claims.
Gesehen am 25.07.2018